If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 9f = 8f Solving -7 + 9f = 8f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-8f' to each side of the equation. -7 + 9f + -8f = 8f + -8f Combine like terms: 9f + -8f = 1f -7 + 1f = 8f + -8f Combine like terms: 8f + -8f = 0 -7 + 1f = 0 Add '7' to each side of the equation. -7 + 7 + 1f = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 1f = 0 + 7 1f = 0 + 7 Combine like terms: 0 + 7 = 7 1f = 7 Divide each side by '1'. f = 7 Simplifying f = 7
| 5=4+v | | 20j=-2(-14j-10)-4j | | 2c=-10 | | f-4=13 | | 3-x/12=18 | | 10.42+11.45-19.3k=15.43-10.1k | | -7u=-7u+5 | | 7n+9=-1+8n | | -7w+7w=0 | | -4r+11r= | | -4t+11r= | | -12m+19.02=-12.7m+6.07 | | 9y+8x=8 | | 3+1(9+y)-5=64 | | 9n-4n= | | 838-1353/8+583/14 | | -18y-18.83-2.16=5.41-16.5y | | 5y-6=42 | | 4t-2t= | | x-45=7 | | 3y+4=3y-8 | | 4x-8i=107yi | | -11m/m | | -16y+18y= | | -19=x/3 | | 6m-6=8m+8-m | | (x-3)(x-2)=7x+30 | | -24=5t+35 | | 2(15r+5)+17=7(7r-18) | | 5w+6-w=7w-2(w-3) | | x/22+7=10 | | cos(2x)=sin(4x) |